Calcium channel blockers: molecular docking and inhibition studies on carbonic anhydrase I and II isoenzymes. Issue 5 (8th March 2021) - Türkeş, Cüneyt; Demir, Yeliz; Beydemir, Şükrü
Abstract: Carbonic anhydrases (CAs) are potent dehydration of carbonic acid and catalyst of the reversible hydration of carbon dioxide. Here, CA I and CA II was purified from human erythrocytes using the simple chromatographic method and determined the interactions between some calcium channel blockers and the enzymes. Molecular docking studies were performed these compounds. It was found that calcium channel blockers (nimodipine, nilvadipine, nitrendipine, isradipine, and nifedipine) exhibit potential inhibitor properties for hCA I and hCA II. IC 50 values of hCA I were in the range of 9.24-58.00 μM, and K i constants were in the range of 7.60 ± 2.68-35.92 ± 16.01 μM. IC 50 values of hCA II were in the range of 70.00-138.60 μM, and K i constants were in the range of 48.30 ± 9.81-162.35 ± 20.47 μM. Nimodipine presented the highest docking score and had competitive inhibition, the benzene and pyridine rings were found to enter the cavity for hCA I. Nifedipine and isradipine did not affect hCA II. Among these drugs, nitrendipine was found to be the most potent inhibitor for hCA I and nimodipine for hCA II. These compounds may be useful for CA inhibitors. Communicated by Ramaswamy H. Sarma